Pengaruh Transfer Pricing, Financial Distress dan Dewan Komisaris Independen terhadap Tax Avoidance - I, Lioni; Yadnya, I Made Sumerta (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2025)
This study aims to analyse the effect of Transfer Pricing, Financial Distress, and Independent Board of Commissioners on Tax Avoidance. This research was conducted by analysing the financial statements of companies in the consumer non-cylical sector listed on the Indonesia Stock Exchange (IDX) during 2018 to 2023. The sample used in this study was 19 companies in the consumer non-cylical sector listed from 2018 to 2023. and sampling was used with Purposive Sampling technique. The data used in this study is secondary data in the form of annual financial reports from each company that is used as a research sample. The variables used in this study are Transfer Pricing as the first independent variable, Financial Distress as the second independent variable, Independent Board of Commissioners as the third independent variable, and Tax Avoidance as the dependent variable. panel data regression method is used as a research methodology in this study. The analysis of research results using the E-Views 12 Student Version Lite application. The results in this study use the selected model, namely the Fixed Effect Model (FEM) The results in this study indicate that Transfer Pricing partially affects Tax Avoidance, Financial Distress has no effect on Tax Avoidance, the Independent Board of Commissioners has no effect on Tax Avoidance, and simultaneously Transfer Pricing, Financial Distress, and the Independent Board of Commissioners affect Tax Avoidance.